2018
DOI: 10.15835/buasvmcn-asb:2018.0019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Extruded Linseed and Walnut Meal Mixture (8:1) on Performance and Plasma Protein Profile in Weaned Piglets

Abstract: The effects of dietary extruded linseed (ELS):walnut meal (WM) mixture (8:1) on performance and plasma protein profile in weaned piglets was evaluated for 21 d. Topigs piglets (n=40; BW=8.02±0.82 kg), age 30±3 days, were allotted into 2 groups and fed 2 diets: control [C, based on corn-triticale-soybean meal (SBM)] and experimental (ELS:WM, where the ELS:WM mixture (8:1) partially replace SBM). Blood samples were collected at 7d and 21d after weaning. The plasma protein profile (total protein, total bilirubin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…However, the diets had no influence (P>0.05) on P plasma concentration. The plasma mineral parameters obtained in our study are in agreement with other studies (Habeanu et al, 2017Gheorghe et al, 2018 CONCLUSION Weaning piglets fed diets with and without Bacillus spp. supplementation had comparable plasma biochemical concentration.…”
Section: Plasma Mineral Profilesupporting
confidence: 92%
See 1 more Smart Citation
“…However, the diets had no influence (P>0.05) on P plasma concentration. The plasma mineral parameters obtained in our study are in agreement with other studies (Habeanu et al, 2017Gheorghe et al, 2018 CONCLUSION Weaning piglets fed diets with and without Bacillus spp. supplementation had comparable plasma biochemical concentration.…”
Section: Plasma Mineral Profilesupporting
confidence: 92%
“…Regarding the difference between periods, we observed that both T-Chol and TG plasma concentration were lower (P<0.05) in day 7 compared with day 17, although this value was within the range of the reference value. The overall T-Chol and TG value obtained in the present study was within the range reported by other authors (Habeanu et al, 2017Gheorghe et al, 2018 Recorded lower glucose value in the blood of weaning piglets in day 7 could be the result of a smaller reserve of fat tissue after birth and higher glucose degradation as the energy source for body warmth maintenance.…”
Section: Plasma Lipidic Profilesupporting
confidence: 91%